The baculovirus antiapoptotic p35 gene also functions via an oxidant-dependent pathway - Sah, Nand K. (The National Academy of Sciences, 1999)
Cellular imbalance in the levels of antioxidants and reactive oxygen species resulting in apoptosis is directly associated with a number of parasitic infections, aging, and several genetic and multifactorial diseases. The baculovirus AcNPV-encoded antiapoptotic p35 gene prevents apoptosis induced by a variety of apoptotic agents in different systems. We demonstrate the ability of the p35 gene to inhibit oxidative stress-induced apoptosis. In vitro cultured Spodoptera frugiperda (Sf9) insect cells infected with wild-type AcNPV carrying the antiapoptotic p35 gene did not undergo apoptosis when subjected to oxidative stress generated by the exogenous application of oxidants or in vivo generation of reactive oxygen species or on direct exposure of cells to UV radiations. An AcNPV mutant carrying a deletion of the p35 gene failed to arrest cell death. Transfection of cells with a recombinant plasmid containing the p35 gene under the transcriptional control of a stress promoter (Drosophila hsp70) was also able to rescue cells from oxidative stress-induced cell death, demonstrating the direct involvement of P35. ESR spin-trapping studies conducted in vitro and in vivo demonstrated that P35 functions directly as an antioxidant by mopping out free radicals and consequently prevents cell death by acting at an upstream step in the reactive oxygen species-mediated cell death pathway.